Legalization and Leadership Strengthening of Karang Taruna Anjereuw: A Participatory Model for Youth Development - Hepi Hastuti; Jelita Purnamasari; Rahmah Agustiani; Andi Masse Dadang (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This community service project aimed to strengthen youth leadership capacity and organizational legitimacy through the establishment of Karang Taruna in Anjereuw Village, Papua. Using a Participatory Action Research (PAR) approach, the program was conducted over 1.5 months in three phases: organizational initiation, cadre training, and legalization through a Village Head Decree issued by the Head of Anjereuw Village (No. 240/001/SK.KEL.ANJW/IX/2025), witnessed by the District Head. Thirty-five youths participated, representing most of the eligible youth in the village, with over 70 percent remaining actively engaged. Activities included participatory meetings, leadership workshops, and facility construction. The program produced three measurable results: (1) legal recognition of Karang Taruna, (2) a public stage for social–cultural events, and (3) a multifunctional youth space supporting small-scale creative business activities. These achievements improved leadership competence, strengthened institutional credibility, and encouraged local entrepreneurship. The findings indicate that combining participatory engagement, organizational development, and practical economic initiatives can provide a sustainable model for youth capacity building and community resilience in rural Papua.